Gender related outcome differences in off-pump coronary artery bypass grafting - Riswan Akram; Friedrich Sobik; Tim Knochenhauer; Sebastian A. Philipp; Jens Brickwedel; Xiaoqin Hua; Beate Reiter; Svante Zipfel; Yvonne Schneeberger; Evaldas Girdauskas; Evaldas Girdauskas; Hermann Reichenspurner; et al. (Frontiers in Cardiovascular Medicine)
ObjectivesSurgical myocardial revascularization shows impaired outcomes in women compared to men. Investigation of gender related outcome differences comprises of different operative strategies potentially hampering interpretation of data. We herein aimed to investigate gender related outcome differences in off-pump coronary artery bypass grafting (OPCAB) only.MethodsBetween 2016 and 2021, 1,075 consecutive patients underwent OPCAB at our center. Of those 880/1,075 were male (81.9%) and 195/1,075 were female (18.1%). Kaplan–Meier analysis was used for investigating differences in survival probabilities. Identification of risk factors was conducted by logistic regression.ResultsMale patients showed a higher rate of reduced LVEF < 35% (88/880, 10% vs. 9/195, 4.61%; p = 0.025) and impaired renal function (creatinine: 1.17 ± 0.76 vs. 1.03 ± 0.59; p = 0.016). In female patients less utilization of both internal mammary arteries was documented (502/880, 57.04% vs. 74/195, 37.94%; p < 0.001). Procedure time (256.13 min vs. 238.02 min; p < 0.001) and number of distal anastomoses (2.40 ± 0.83 vs. 2.11 ± 0.82; p < 0.001) were lower in female patients. 30-day mortality (16/880, 0.34% vs. 4/195, 0.51%; p = 0.77) and rates of disabling stroke (3/880, 1.81% vs. 1/195, 2.05%; p = 0.55) were similar between groups. In logistic regression analysis age (OR 1.079; CI 1.001- 1.162; p = 0.047) and impaired renal function (OR 1.495; CI 1.090–2.051; p = 0.013) were identified as independent risk factors for 30-day mortality.ConclusionsMale and female patients present similar 30-day outcomes after OPCAB suggesting a potential benefit of OPCAB in female patients. However, female patients receive more saphenous vein grafts compared to men, which may lead to impaired long-term outcomes.